Use of New Extensionist Kit and Global Good Practice Notes on extension in curricula of 63 agricultural universities in India and one South African university - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The New Extensionist Learning Kit, a set of training modules designed to improve functional skills of agricultural extension agents, and a collection of standardized, easy to understand, extension materials called “Global Good Practice notes”, both produced with support from PIM between 2014 and 2020, were incorporated into the Indian national extension curriculum (to be used by 63 universities) and into a university’s curriculum in South Africa.